Governance of Financial Assistance to Political Parties Based on Good Governance Principles in Indonesia - Cahyo Ariawan; Bahrullah Akbar; Mansyur Achmad; Nuryanto Nuryanto (Budapest International Research and Critics University, 2022)
The problem of this research is that the government's indecisiveness in giving sanctions makes political parties remain negligent in providing financial accountability reports for political parties for state subsidies. When the financial accountability reports from state subsidies are not in accordance with existing regulatory provisions, it can be ascertained how the form of financial accountability of political parties for funding sources that do not come from the state can be ascertained. Then another problem, namely the inability of the government to manage the financial assistance of political parties by providing accountability and transparency of political parties is accused of being one of the root causes of the management of financial assistance of political parties that are not in accordance with the principles of good governance. This research on the governance of the provision of financial assistance to political parties based on the principles of good governance uses a qualitative descriptive research approach. Qualitative descriptive research is research that is included in the type of qualitative research. In the aspect of responsive and responsible leadership, the three actors, both civil actors, governance and political parties, have not yet seen a leadership figure who through political will and his leadership role has become a driving force with certain instruments to realize the support of creating a synergistic connectedness. This synergistic relationship fosters a mutually influencing response in order to support the realization of the conception of good governance in the management of political party financial assistance. The lack of traces of breakthroughs made by the leadership figures of the three actors, so that leadership practices are still passive to actually realize the governance of political party financial assistance in accordance with the principles of good governance. The most dominant aspect of power where the government has not been able to maximally influence political parties so that the management of financial assistance can be more accountable and transparent.